Pengembangan Teori Tekanan Lateral Aktif pada Dinding Penahan Tanah Menggunakan Metode Elemen Hingga - Hizbulmalik, Ziyan; Lim, Aswin (Universitas Ibn Khaldun, 2025)
Estimating the value of lateral earth pressure acting on a rigid retaining wall is very important in the design of geotechnical structures. Various theories have been developed to calculate lateral earth pressure, each with it is own methodologies, equations, and assumptions. However, none of the studies above considered the lateral earth pressure equation based on the finite element method. In this study, conventional methods and finite element methods are used to determine the amount of active lateral earth pressure that occurs in the retaining wall, and a finite element method-based equation of active lateral earth pressure is proposed. Parametric experiments were also conducted to determine the active lateral earth pressure distribution's response to various parameters.